Time series of environmental parameters of habitats along the Schleswig-Holstein Baltic Sea (2018 et seq) - Christian Lieberum; Claas Hiebenthal; Rolf Karez (PANGAEA, 2024)
The here presented data time-series are connected to the publication "Environmental parameters of shallow water habitats in the SW Baltic Sea" (Franz, M. et al. 2019b). Since 2019 a number of stations were added, and, hence, new time-series started. Every year a new dataset will be published including both, old and new stations. The following abstract is revised from Franz, M. et al. (2019b): The coastal areas of the Baltic Sea represent highly variable environments. In order to record the environmental conditions in shallow water habitats of the SW Baltic Sea, a monitoring program was established. The monitoring sites are located along the Baltic Sea coast of Schleswig-Holstein, Germany. Along the coast, 23 stations were established, where samplings for dissolved inorganic nutrient concentrations are conducted. Here, twice per month, water samples are collected in a water depth of 0.5 m. The samples are analysed for the concentration of dissolved inorganic nutrients (total oxidized nitrogen, nitrite, ammonia, phosphate and silicate) by UV/VIS spectroscopy using a continuous flow analyser (type QuAAtro 30; comp. SEAL Analytical, Hamburg, Germany. The system is equipped with a SEAL XY-2 autosampler). Quality control for nutrient measurements is ensured by certified reference material (CRM) by KANSO TECHNOS CO, LTD, Osaka, Japan. Additionally, at four shallow water stations (Booknis Eck, Bülk, Behrensdorf and Katharinenhof) temperature, salinity and dissolved oxygen are continuously logged at 2-3 m depth by self-contained data loggers. These are: (I) MiniDOT loggers (Precision Measurement Engineering; http://pme.com; ±10 μmol L-1 or ±5 % saturation) including antifouling copper option (copper plate and mesh) to measure dissolved oxygen concentration and (II) DST CT salinity & temperature loggers (Star-Oddi; http://star-oddi.com; ±1.5 mS cm-1) to record the conductivity. Both sensor types additionally record water temperature with an accuracy of ± 0.1 °C. The sampling interval was set to 30 minutes for all parameters. Another seven stations for continuous recordings of environmental parameters (again: temperature, salinity, dissolved oxygen) with the same two types of sensors were installed at 4-6 m depth in the context to the long-term monitoring project RegLocDiv (Regional-Local-Diversity) by M. Wahl (Franz, M. et al. 2019a) and included into this data set. These stations are at: Falshoeft, Booknis Eck, Schoenberg, Westermakesdorf, Staberhuk, Kellenhusen and Salzhaff (abandoned in 2023). Since 2021, in the context of implementing a reef monitoring to fulfil obligations by the EU Habitats Directive, step-by-step, eleven further stations were installed at reefs in the Schleswig-Holstein Baltic Sea. These are at: Platengrund (14 m depth) and Mittelgrund (8 m) (both since 2021), at Walkyriengrund (9 m), Brodtener Ufer (8 m), Außenschlei (11 m), Kalkgrund (8 m), Stollergrund (7.5 m) and Flueggesand (10 m) (all since 2022), as well as at Gabelsflach (10 m), Sagasbank (8.5 m) and Stabehuk (11.5 m) (all since 2023). Again, at all of these 11 stations, temperature, salinity and dissolved oxygen are continuously logged by self-contained data loggers: Conductivity (and temperature) is logged by HOBO® Salt Water Conductivity/Salinity Data Logger (Onset Computer Corporation, Bourne, MA, USA; https://www.onsetcomp.com) using the U2X protective housing to prevent fouling on the sensors. The same MiniDOT loggers (Precision Measurement Engineering) as at the above mentioned more shallow stations (including antifouling copper plate and mesh) are used to measure dissolved oxygen concentration. Dissolved oxygen concentration data measured by the MiniDOT loggers are corrected for a depth of 5 m (or 2,5 m on the shallow stations) using the software provided by the manufacturer. Additionally, a manual compensation for salinity was calculated (see details in Franz, M. et al. 2019b). Quality control was carried out by spike and gradient tests, following recommendations of SeaDataNet quality control procedures (see https://seadatanet.org/Standards/Data-Quality-Control). All data values were flagged according to applied quality checks using the following flags: 1 = Pass, 2 = Suspect, 3 = Fail, 4 = Visually suspect, 5 = Salinity compensation fail (further explanations can be found in Franz, M. et al. 2019b). The project is funded by the LfU (Landesamt für Umwelt, Schleswig-Holstein, Germany). Main responsible persons are C. Hiebenthal, C. Lieberum, F. Weinberger and R. Karez. Responsible for the nutrient analysis: N. Stärck; Responsible for taking the water samples: C. Lieberum and D. Bürger.